2017
DOI: 10.1016/j.jecp.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessing a continuum of lexical–semantic knowledge in the second year of life: A multimodal approach

Abstract: Behavioral dissociations in young children’s visual and haptic responses have been taken as evidence that word knowledge is not all-or-none but instead exists on a continuum from absence of knowledge, to partial knowledge, to robust knowledge. This longitudinal study tested a group of 16- to 18-month-olds, 6 months after their initial visit, to replicate results of partial understanding as shown by visual–haptic dissociations and to determine whether partial knowledge of word–referent relations can be leverage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 70 publications
(119 reference statements)
3
21
0
Order By: Relevance
“…Therefore, it may be recommended and beneficial that both results from pointing and looking measures, and the proportion of absent pointing responses should be reported to interpret obtained data in more detail. In fact, some researchers conducted a similar task using both modalities as dependent variables and compared differences between them (Abbot- Smith et al, 2017;Gurteen et al, 2011;Hendrickson & Friend, 2013;Hendrickson et al, 2015Hendrickson et al, , 2017. Future research is needed to investigate a more nuanced relationship between looking and manual measurements.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, it may be recommended and beneficial that both results from pointing and looking measures, and the proportion of absent pointing responses should be reported to interpret obtained data in more detail. In fact, some researchers conducted a similar task using both modalities as dependent variables and compared differences between them (Abbot- Smith et al, 2017;Gurteen et al, 2011;Hendrickson & Friend, 2013;Hendrickson et al, 2015Hendrickson et al, , 2017. Future research is needed to investigate a more nuanced relationship between looking and manual measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Hendrickson and Friend (2013) claimed that looking and manual responses reflect different levels of word understanding, based on connectionist studies (Munakata, 2001; Munakata & McClelland, 2003). Hendrickson et al (2017) further revealed that, in the familiar word comprehension task, words for which toddlers did not execute reaching at 16 months were still unknown at 22 months, whereas words for which 16‐month‐olds reached to distracter rather than target stimulus were more likely to be known six months later. These findings indicate that the absence of manual responses itself has insightful information on early word knowledge (e.g., fragility or uncertainty).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations